Focus of Attention in Children with ASD - E.G. Karimulina; N.G. Khlyustova (Moscow State University of Psychology and Education, 2020)
The special way of understanding the world and the brain mechanisms of cognitive impairment in children with autism spectrum disorders (ASD) are becoming the core topics in the autism research. The article presents a study of the general characteristics of attention in children of primary school age with ASD using instruments aimed at detecting impairments of attention parameters: Schulte Tables, Go/No Go Task, Kraepelin's Arithmetic Test, Stroop Test used to study the focus of attention in the context of the interference of verbal and object stimuli. Results of study of attention in children with ASD seemed to be ambivalent. Children with ASD are successful in performing the Schulte Tables; on the contrary, the Go/No Go Task shows the difficulties of performing the tasks and inhibition of dominant response. Different degrees of unstable focus of attention in tasks on visual perception also shown. The features of focusing attention in conditions of interference require further research. Preliminary results showed that the focus of attention in younger schoolchildren with ASD is associated with a preference for verbal rather than object characteristics of visual stimuli.